SYNERGY OF INTERNAL AND EXTERNAL FACTORS IN HOLISTIC STUDENT DEVELOPMENT - Rohbiah, Rohbiah; Ramli, M. (STKIP PGRI Situbondo, 2025)
Factors influencing student development consist of two main aspects: internal and external factors. Internal factors include physical, psychological, and mental conditions such as health, intelligence, motivation, interest, attention, and learning readiness. Meanwhile, external factors, such as prayer, encompass the influence of family, school, community, and spirituality. This journal discusses the interconnection between these factors in supporting or hindering the learning process. The family plays a foundational role in shaping the child's character, while schools and communities contribute through facilities, teaching methods, and social norms. A holistic approach involving spiritual support is also considered effective in enhancing students' emotional resilience. This study concludes that the synergy between internal and external factors is key to achieving optimal educational success. A deeper understanding of these factors is expected to assist teachers, parents, and policymakers in creating an educational ecosystem supporting students' holistic development.